A program for data visualization for small technical systems - Puhanovskyi, Oleh; Panasenko, Vladimir (MDPC Publishing, 2023)
Mini SCADA for automated control systems of laboratory installations and small technological processes. The work was performed as part of a professional development course. This program provides control of microprocessor controllers that are connected to the serial port of a personal computer. The developed program allows you to use any devices connected to a serial port if there is a description of the exchange protocol.
Keywords: technical systems; small technical systems; data visualization; a program for data visualization; mini SCADA; technological processes